Interferon-induced transmembrane protein 1 (IFITM1) overexpression enhances the aggressive phenotype of SUM149 inflammatory breast cancer cells in a signal transducer and activator of transcription 2 (STAT2)-dependent manner. Issue 1 (December 2016) - Ogony, Joshua; Choi, Hye; Lui, Asona; Cristofanilli, Massimo; Lewis-Wambi, Joan
Abstract Background Inflammatory breast cancer (IBC) is a very aggressive and lethal subtype of breast cancer that accounts for about 4 % of all breast cancers diagnosed in the United States. Despite the efforts of several investigators to identify the molecular factors driving the aggressive phenotype of IBC, a great deal is still unknown about the molecular underpinnings of the disease. In the present study, we investigated the role of interferon-induced transmembrane protein 1 (IFITM1 ), a well-known interferon-stimulated gene (ISG), in promoting the aggressiveness of SUM149 IBC cells. Methods Western blot and real-time polymerase chain reaction analyses were performed to assess the protein and messenger RNA (mRNA) levels ofIFITM1 and other ISGs in three IBC cell lines: SUM149, MDA-IBC-3, and SUM190.IFITM1 expression and cellular localization were assessed by using immunofluorescence, while the tumorigenic potential was assessed by performing cell migration, invasion, and colony formation assays. Small interfering RNA and short hairpin RNA knockdowns, enzyme-linked immunosorbent assays, and luciferase assays were performed to determine the functional significance of IFITM1 and signal transducers and activators of transcription 1 and 2 (STAT1/2) in SUM149 cells. Results We found thatIFITM1 was constitutively overexpressed at the mRNA and protein levels in triple-negative SUM149 IBC cells, but that it was not expressed in SUM190 and MDA-IBC-3 IBC cells, and that suppression of IFITM1 or blockade of the IFNα signaling pathway significantly reduced the aggressive phenotype of SUM149 cells. Additionally, we found that knockdown of STAT2 abolished IFITM1 expression and IFITM1 promoter activity in SUM149 cells and that loss of STAT2 significantly inhibited the ability of SUM149 cells to proliferate, migrate, invade, and form 2-D colonies. Notably, we found that STAT2-mediated activation of IFITM1 was particularly dependent on the chromatin remodeler brahma-related gene 1 (BRG1), which was significantly elevated in SUM149 cells compared with SUM190 and MDA-IBC-3 cells. Conclusions These findings indicate that overexpression ofIFITM1 enhances the aggressive phenotype of triple-negative SUM149 IBC cells and that this effect is dependent on STAT2/BRG1 interaction. Further studies are necessary to explore the potential ofIFITM1 as a novel therapeutic target and prognostic marker for some subtypes of IBCs.